Lowering the B1 threshold for improved BEAR B1 mapping. Issue 3 (4th April 2015) - Jordanova, Kalina V.; Nishimura, Dwight G.; Kerr, Adam B.
Abstract : Purpose: Accurate measurement of the nonuniform transmit radiofrequency field is necessary for magnetic resonance imaging applications. The radiofrequency field excitation amplitude ( B 1 ) is often obtained by acquiring a B 1 map. We modify the B 1 estimation using adiabatic refocusing (BEAR) method to extend its range to lower B 1 magnitudes. Theory and Methods: The BEAR method is a phase‐based B 1 mapping method, wherein hyperbolic secant pulses induce a phase sensitivity to B 1 . The measurable B 1 range is limited due to the adiabatic threshold of the pulses. We redesign the method to use flattened hyperbolic secant pulses, which have lower adiabatic thresholds. We optimize the flattened hyperbolic secant parameters to minimize phase sensitivity to frequency variations. Results: We validate the performance of the new method via simulation and in vivo at 3T, and show that for n ≤ 8, accurate B 1 maps can be acquired using reduced nominal peak B 1 values. Conclusion: The adiabatic threshold for the BEAR method is reduced with flattened hyperbolic secant pulses, which are optimized for accurate phase‐to‐ B 1 mapping over a frequency range, and allow for lower nominal B 1 values. At 3T, the nominal B 1 is decreased by 52% and the sensitivity to B 1 is increased by a factor of 3.8. This can improve the method's applicability for measurement of low B 1 . Magn Reson Med 75:1262–1268, 2016. © 2015 Wiley Periodicals, Inc.